Design of a Low-Power Voltage Regulator for RFID Applications - Heidrich, Jürgen; Brenk, Daniel; Essel, Jochen; Heinrich, Matthias; Jung, Melanie; Hofer, Günter; Holweg, Gerald; Weigel, Robert; Fischer, Georg (IEEE R8 International Conference On Computational Technologies in Electrical And Electronics Engineering 2010 (SIBIRCON 2010), 2010)
This paper briefly reviews common state-of-the-art architectures of voltage regulators and their applicability to RFID. After that the design of a Low Drop-out (LDO) regulator using active resistances is presented, especially suitable for RFID applications. The chip is designed based on a 0.13 μm CMOS technology.
elib2cris::1512001600,heidrich2010d
Keywords: Radiofrequency identification; Regulators; Transponders; Voltage control; CMOS integrated circuits; low-power electronics; voltage regulators; RFID; CMOS technology; low drop-out regulator; low-power voltage regulator; LDO; reference circuit; low-voltage; reference voltage; wireless sensing